Factors Influencing Patient Satisfaction - Desmon Desmon; Hasbullah Hasbullah; Yudhinanto Yudhinanto (Indonesian Journal of Global Health Research, 2024)
The quality of health services needs to be improved because of the needs of the community in accordance with the standards of resource utilization in a fair, efficient, and effective manner. With the limitations of the government and community, health services are still carried out safely and satisfactorily in accordance with good norms and ethics. Health services in hospitals, health centers, clinics or other health institutions are components that are interrelated, interdependent, and influence each other. This study aims to determine the effect of reliability, responsiveness, and assurance variables simultaneously and partially on patient satisfaction at the Ismadana Muaradua Clinic. This study uses a quantitative method with 100 respondents. Data was collected directly from respondents using a previously prepared questionnaire The analysis tool uses multiple linear regression. The results of the study showed that both simultaneously (F-test) and partially (t-test) concluded that the variables Reliability (X1), Responsiveness (X2), and Assurance (X3) have a significant effect on Patient Satisfaction (Y).